2013
DOI: 10.4070/kcj.2013.43.6.429
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Closure of the Acquired Gerbode Shunt Using the Amplatzer Duct Occluder in a 3-Month Old Patient

Abstract: The Gerbode shunt, known as the left ventricle to the right atrial communication, is a rather rare finding, following surgical closure of septal defects. Even though the surgical closure is accepted as a treatment of choice, we report a successful percutaneous transcatheter closure of the Gerbode shunt in a 3-months old baby who weighed 3 kilograms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Aetiologies of the LV-RA shunts were congenital in 32 (26.4%) cases [ 6 , 7 , 9 28 , 30 32 ], acquired in 88 (72.7%) cases [ 2 , 3 , 7 , 8 , 18 , 31 , 33 68 , 70 90 , 92 , 94 – 104 , 106 108 , 110 , 111 ] and unknown in 1 (0.8%) patient [ 112 ], respectively. A significant difference was noted in the percentages between congenital and acquired LV-RA shunts (χ 2 = 52.3, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Aetiologies of the LV-RA shunts were congenital in 32 (26.4%) cases [ 6 , 7 , 9 28 , 30 32 ], acquired in 88 (72.7%) cases [ 2 , 3 , 7 , 8 , 18 , 31 , 33 68 , 70 90 , 92 , 94 – 104 , 106 108 , 110 , 111 ] and unknown in 1 (0.8%) patient [ 112 ], respectively. A significant difference was noted in the percentages between congenital and acquired LV-RA shunts (χ 2 = 52.3, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…The first successful series of patients operated on with a left ventricular to right atrial shunt was reported by Gerbode et al . There are a few case reports of percutaneous closure of acquired Gerbode shunts . There is a small series of four cases of post‐surgical Gerbode defects closed successfully with various devices.…”
Section: Discussionmentioning
confidence: 99%
“…These shunts are traditionally closed surgically with high incidence of complete heart block. There are case reports and small series of mostly acquired and few congenital Gerbode defects closed percutaneously with various types of devices . We report a small series of 12 cases of only congenital Gerbode defects closed with Amplatzer duct occluder II (ADO II) which is specially designed to close long tubular duct in infants.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the surgical closure is accepted as a treatment of choice[ 12 ], some successful transcatheter closures for Gerbode defect have been reported. There is a paucity of information in the existing literature on transcatheter therapy for this type of defect.…”
Section: Discussionmentioning
confidence: 99%
“…Another device, amplatzer septal occluder (ASO) commonly used for atrial septal defect closure, also being used to close Gerbode defect complicated from mitral valve surgery with marked improvement in exercise tolerance[ 13 ]. The smallest patient reported, a 3-mo old baby with an acquired Gerbode shunt after VSD patch closure, was treated using an amplatzer duct occluder (ADO) with complete closure achieved 2 wk after device deployment and good long term follow-up[ 12 ]. Recently, a report of 12 Gerbode defect patients that were transcatheterly closed with ADO II showed satisfactory outcomes[ 14 ].…”
Section: Discussionmentioning
confidence: 99%